Effect of creatine and weight training on muscle creatine and performance in vegetarians - Burke, D. G.; Chilibeck, P. D.; Parise, G.; Candow, D. G.; Mahoney, D.; Tarnopolsky, M. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: To compare the change in muscle creatine, fiber morphology, body composition, hydration status, and exercise performance between vegetarians and nonvegetarians with 8 wk of creatine supplementation and resistance training. METHODS: Eighteen VG and 24 NV subjects (19-55 yr) were randomly assigned (double blind) to four groups: VG + creatine (VGCr, N=10), VG + placebo (VGPl, N=8), NV + creatine (NVCr, N=12), and NV + placebo (NVPl, N=12). Before and at the end of the study, muscle biopsies were taken from the vastus lateralis m, body composition was assessed by DXA, and strength was assessed using 1-RM bench press and leg press. Subjects participated in the same 8-wk resistance-training program. Creatine dosage was based on lean tissue mass (0.25 g.kg(-1) LTM.d(-1) x 7 d; 0.0625 g.kg(-1) LTM.d(-1) x 49 d). RESULTS: Biopsy samples indicated that total creatine (TCr=free Cr + PCr) was significantly lower in VG compared with NV at baseline (VG=117 mmol.kg(-1); NV=130 mmol.kg(-1); P<0.05). For Cr subjects, there was a greater increase in PCr, TCr, bench-press strength, isokinetic work, Type II fiber area, and whole-body lean tissue compared with subjects on placebo (P<0.05). Vegetarians who took Cr had a greater increase in TCr, PCr, lean tissue, and total work performance than nonvegetarians who took Cr (P<0.05). The change in muscle TCr was significantly correlated with initial muscle TCr, and the change in lean tissue mass and exercise performance. These findings confirm an ergogenic effect of Cr during resistance training and suggest that subjects with initially low levels of intramuscular Cr (vegetarians) are more responsive to supplementation.